Optimalisasi Tracking Rekam Medis Dengan Barcode di Puskesmas Lendah II - Ilmi, Laili Rahmatul; Praptana, Praptana; Sari, Rizky Yuspita; Herawan, Heri; Pramono, Angga Eko; Indriyani, Meita (Jurnal Ilmiah Perekam dan Informasi Kesehatan Imelda (JIPIKI), 2023)
In 2014, primary health centres Lendah II was implemented health information system for primary care (Simpus). the use of simpus can help the physician and health practicioners entry data of patient, import dan export data and also improved theirs performance. The implementation of medical records for primary health centres an important role in managing patient data. The use of technology and information systems in the health sector has an impact on optimizing services. One of them is by utilizing a barcode system to support storage at primary health centres Lendah II This study aims to help the storage tracking system in the filing room using barcodes. Data capture with FGD for needs analysis, then application design and trials. This research uses research and develompent. The results of the study by making class diagrams, barcode applications and examples of barcodes applied to poly service names and medical record numbers. Barcodes will be printed and affixed to the patient's medical record to facilitate tracking of the The barcode of the patient's medical record number will also be affixed to the patient's BPJS card, making it easier for officers to check the patient's medical record number on the simpus. There is a scanner reader tool that will make it easier for officers to read barcode codes.